2018
DOI: 10.1038/s41386-018-0063-3
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin reduces a chemosensory-induced stress bias in social perception

Abstract: Social transmission of fear is not restricted to visual or auditory cues, but extends to the phylogenetically more ancient olfactory domain. Anxious individuals exhibit heightened sensitivity towards chemosensory stress signals in sweat; however, it is still unknown whether endogenous neuromodulators such as the peptide hormone oxytocin (OXT) influence the chemosensory communication of stress. Here, we investigated whether OXT selectively diminishes behavioral and neural responses to social chemosensory stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 51 publications
2
35
2
Order By: Relevance
“…elevated oxytocin, via its action in the AON, can enhance recognition of social odor cues, such as those of partners or kin (Oettl et al, 2016). In humans, oxytocin also modulates responsiveness to social odors (Maier et al, 2019), though a link to receptors in AON has not been determined.…”
Section: Neural Circuits and Odor Perceptionmentioning
confidence: 99%
“…elevated oxytocin, via its action in the AON, can enhance recognition of social odor cues, such as those of partners or kin (Oettl et al, 2016). In humans, oxytocin also modulates responsiveness to social odors (Maier et al, 2019), though a link to receptors in AON has not been determined.…”
Section: Neural Circuits and Odor Perceptionmentioning
confidence: 99%
“…Other assessments have focused on effects of chemical signals in relation to real-life settings such as influencing social judgment [29], and clinical performance of dental students [30]. Similarly, recordings of brain activity have been assessed with findings indicating higher event-related potentials at various time points (e.g., [31,32]), increased amygdala activity [33,34], and recruiting a wider network of brain regions in relation to empathy [35].…”
Section: Introductionmentioning
confidence: 99%
“…A better understanding of the underlying mechanism of action is important because an increasing number of studies indicate that the potential clinical effects of OXT are person-and context-dependent (Bartz, Zaki, Bolger, & Ochsner, 2011;Olff et al, 2013) and vary as a function of attachment organization and social support. Furthermore, it has been shown that OXT not only modulates activity in the insular cortex (Striepens et al, 2012;Wigton et al, 2015) and VMPFC (Aoki et al, 2015;Labuschagne et al, 2012) but also reduces the neural response to stress-associated signals (Maier et al, 2018) and painful stimuli in the amygdala (AMY) (Paloyelis et al, 2016). Furthermore, it has been shown that OXT not only modulates activity in the insular cortex (Striepens et al, 2012;Wigton et al, 2015) and VMPFC (Aoki et al, 2015;Labuschagne et al, 2012) but also reduces the neural response to stress-associated signals (Maier et al, 2018) and painful stimuli in the amygdala (AMY) (Paloyelis et al, 2016).…”
mentioning
confidence: 99%